Learning from World Bank History : Agriculture and Food-Based Approaches for Addressing Malnutrition - World Bank Group (Washington, DC, 2014)
The purpose of this paper is to provide forward-looking recommendations for linking agriculture and nutrition by looking back over the 40 years since both nutrition and rural development began at the Bank in 1973. This paper sets out to explore whether what is currently being suggested has been attempted in the past; in what circumstances, with what sort of support or commitment, by what actors, and with what results. Throughout, the World Bank is a case study set within the larger development aid architecture due to its role as one of the largest actors in agriculture and nutrition investments in developing countries around the nutrition initially was housed in the Population department (1972-75), and then moved to Agriculture and Rural Development (1975-79). Since 1979 it has been housed with health and other human development world. The initial motivation was to showcase the depth of historical resources available in the World Bank Group Archives, and to demonstrate how they can be used to inform current practice. Several lessons learned primarily from the World Bank experience are applicable to the Bank's current commitment to nutrition-sensitive agriculture, as well as to the development community at large, that is tackling the same agenda.